Non-uniqueness for second order elliptic operators. (January 2016) - Metafune, Giorgio; Sobajima, Motohiro; Spina, Chiara
Abstract: We show an abstract method to construct different realizations of abstract operators generating a strongly continuous semigroup and apply it to several second order elliptic operators with singular coefficients.